A descriptive study of non-melanoma skin cancers in patients attending Charlotte Maxeke Johannesburg Academic Hospital and Helen Joseph Hospital from July 2013 to June 2016 - Ndakunda, Julia Ndeshihafela (My University, 2021)
Introduction: Non-melanoma skin cancers (basal cell carcinomas and squamous cell carcinomas) are skin cancers derived from epidermal keratinocytes, and they are the most common tumours in humans in predominantly white populations. There are very few studies done on these cutaneous malignancies in South Africa. Aim of study: The aim of this study was to describe the characteristics of non-melanoma skin cancers (NMSCs) in patients attending Charlotte Maxeke Johannesburg Academic Hospital and Helen Joseph Hospital. Methods: A retrospective case review of histologically confirmed cases of non-melanoma skin cancers in patients seen at Charlotte Maxeke Johannesburg Academic Hospital and Helen Joseph Hospital between July 2013 and June 2016. Results: A total of 356 cases of histologically confirmed non-melanoma skin cancers were reviewed. Of these, 74.7% were basal cell carcinomas and 25.3% were squamous cell carcinomas. Most non-melanoma skin cancers occurred in elderly male patients. The majority of non-melanoma skin cancers (74.4%) were observed on the sun exposed areas of the body. There was a statistically significant difference in the distribution (body site) of NMSCs in males and females (p=0.018 for basal cell carcinomas, and p=0.014 for squamous cell carcinomas). Most basal cell carcinomas showed a mixed histological pattern (28.2%), whilst most squamous cell carcinomas (60%) were moderately differentiated invasive squamous cell carcinomas. Nine percent (n=32) of patients had additional risk factors associated with development of non-melanoma skin cancers. HIV infection was associated with an increased risk of developing squamous cell carcinoma and not basal cell carcinoma. Conclusion: Most non-melanoma skin cancers (NMSCs) occurred in elderly male patients, and were observed on the sun exposed areas of the body. Basal cell carcinomas (BCC) were the most common NMSC. There was a difference in the distribution (body site) of NMSCs in males and females. The predominant mixed histological pattern of BCC and the moderately differentiated SCC histological subtype in this study are associated with aggressive and intermediate clinical behavior, respectively. Meticulous recording and reporting of these skin cancers will aid in further research of these cancers, which will result in proper allocation of healthcare resources required to diagnose, treat and prevent these highly preventable skin cancers
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Dermatology, 2021